The Polokwane conference and South Africa’s second political transition: tentative conclusions on future perspectives - Venter, J. C. M. (Koers, 2008)
In this phase of South Africa’s second political transition (manifesting characteristics of political decay) it looks as if the ANC is becoming more dominant, hegemonic and ideological, with added neo-patrimonial tendencies that are becoming more overt in an oligarchic manner. This article analyses the ANC’s Polokwane conference (qualitatively and deductively) as part of South Africa’s second political transition since 1994 and postulates potential outcomes (scenario perspectives).